Pyrrolidinium containing perovskites with thermal stability and water resistance for photovoltaics. Issue 36 (30th August 2019) - Xu, Alex Fan; Wang, Ryan Taoran; Yang, Lory Wenjuan; Liu, Na; Chen, Qi; LaPierre, Ray; Isik Goktas, Nebile; Xu, Gu
Abstract : A pyrrolidinium based perovskite with both excellent thermal stability and moisture resistance. Abstract : The commonly employed methyl-ammonium containing perovskites are unstable at high temperature or under moisture attack, thus limiting their commercial applications. To overcome this barrier, a new perovskite possessing both thermal stability and water resistance has been constructed, involving pyrrolidinium rings (CH2 )4 NH2 PbI3 (PyPbI3 ), through a simple solution-processing method. It presents not only prolonged moisture resistance and a favorable bandgap of 1.80 eV, as determined by P-XRD and UV absorption, but also excellent thermal stability, as verified via the in situ XRD technique. The new structure may be applicable to perovskite solar cells with improved thermal stability and water resistance.